Mid-term Patency of the Great Saphenous Bypass to Aorta vs. Non-aortic Arteries in Stanford Type A Aortic Dissection Surgery With Concomitant CABG - Wang, Maozhou; Jia, Songhao; Pu, Xin; Sun, Lizhong; Gong, Ming; Zhang, Hongjia (Frontiers in Cardiovascular Medicine, 2021)
Background: Stanford type A aortic dissection (STAAD) is often associated with coronary artery problems, requiring coronary artery bypass grafting (CABG). However, the prognosis of different proximal graft locations remains unclear. Methods: From May 2015 to April 2020, 62 acute STAAD patients who underwent aortic surgery concomitant with CABG were enrolled in our study. Aortic bypass was defined as connecting the proximal end of the vein bridge to the artificial aorta (SVG-AO); non-aortic bypass was defined as connecting the proximal end of the vein bridge to a non-aorta vessel, including left subclavian artery, left common carotid artery and right brachiocephalic artery (non-SVG-AO). We compared early- and mid-term results between patients in the above two groups. Early results included death and bleeding and mid-term results graft patency, aortic-related events, and bleeding. Grafts were evaluated by postoperative coronary computed tomography angiography. According to the Fitzgibbon classification, grade A (graft stenosis < 50%) is considered a patent graft. Univariate and multivariate analyses were performed to assess differences between aortic and non-aortic bypass in STAAD. Results: SVG-AO and non-SVG-AO were performed in 15 and 47 patients, respectively. There was no significant difference in death (log-rank test, p=0.426) or bleeding (p=0.766) between the two groups in the short term. One year of follow-up was completed in 37 patients (8 in the SVG-AO group and 29 in the non-SVG-AO group), among which 14/15 (93.3%) grafts were patent in the SVG-AO group and 32/33 (97.0%) grafts in the non-SVG-AO at 1-week, without a significant difference (p=0.532). At 3 months, 12/13 (92.3%) grafts were patent in the SVG-AO group and 16/32 (50.0%) grafts in the non-SVG-AO, with a significant difference (p=0.015), and12/13 (92.3%) grafts in the SVG-AO group and 15/32 (46.9%) grafts in the non-SVG-AO group were patent, with a significant difference. Multivariate analysis showed proximal aortic bypass and dual anticoagulation to be protective factors for the one-year patency of grafts. Conclusion: In patients with aortic dissection concomitant with CABG, no differences between SVG-AO or SVG-non-AO in early outcomes were detected, but SVG-AO may have higher mid-term patency.